Bridging the gap: Unmet needs in interventional nephrology in Pakistan - Ayub, Haroon; Qayyum, Ahad; Clark, Ruri; Richard, Marie; Qureshi, Junaid; Khan, Ali; Azhar, Muhammad; Ahmad, Saeed (Pakistan Journal of Kidney Diseases, 2022)
Nephrology is a multidisciplinary team specialty that provides care for patients with established renal disease requiring Renal Replacement Therapy and renal transplantation. There has been enormous progress in RRT and interventional procedures have now become an integral part of Renal medicine training curriculum. Historically, nephrologists have relied on other specialties to perform these procedures. This reliance often caused inefficiency in patient care and therefore led to the birth of sub-specialty of ‘Interventional Nephrology’ (IN). We here describe the various efforts being done in Pakistan for promortion and establishment of IN as a routine part of training of the nephrology residents and as a separate subspeciality . We here also highlight the efforts being imparted by the Pakistan Society of Nephrology and sister units abroad in training the nephrologists and residents.